Pengendalian Bahaya dan Risiko K3 Menggunakan Metode HIRADC dan FTA Pada Industri Kerupuk - Roberta H. A. Tanisri; Kharisno Kharisno; Denny Siregar (Journal of Industrial and Engineering System, 2022)
CV Irma is one of the traditional cracker processing industries located in the city of Bekasi. The production process of processing these crackers is still carried out traditionally. This can cause gaps in the occurrence of work accidents due to processes and ways of working that still use manual processes. The purpose of this study is to provide proposals for K3 risk control to minimize the potential dangers and risks that exist in the cracker production process. The study was conducted using the HIRADC (Hazard Identifcation, Risk Assessment and Determining Control) and FTA (fault tree analysis) methods to determine the root cause of a kerrja accident with a high risk value. The results of this study were obtained to be able to reduce the risk level of the existing potential hazards, from the high, medium, and low value risk levels from the comparison before and after control.